M. Amin Abdullah's contribution: Toward an integrated and interconnected Islamic education - Sanial Habibi; Eko Purnomo; Zaki Faddad Syarif Zain (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2024)
Islamic education in Indonesia faces significant challenges in adapting to the rapid development of knowledge and globalization. Traditional approaches often need to be revised to prepare students to be competitive in the modern era. This study aimed to analyze the concept of integration and interconnection in M. Amin Abdullah’s thoughts and his contribution to developing the Islamic education paradigm in Indonesia. The main focus was to explore how these two concepts could enhance the relevance of Islamic education in addressing the challenges of the globalization era. This study used a library research method by collecting and reviewing secondary literature, including M. Amin Abdullah’s writings, journal articles, academic books, and other supporting documents related to the research topic. Data were analyzed through content analysis to identify key themes related to integration and interconnection and the challenges and opportunities in their application in Islamic education. The study's results indicate that integration and interconnection in M. Amin Abdullah's thinking significantly contribute to developing an adaptive, holistic, and relevant Islamic education paradigm in line with the progress of science and technology. However, the study also identifies challenges in implementing these concepts, particularly regarding policy support and curriculum adaptation in Islamic education. Keywords: Integration, Interconnection, Islamic education, M. Amin Abdullah, paradigm